State-Dependent Transmission of Monetary Policy in the Euro Area - Jan Pablo Burgard; Matthias Neuenkirch; Matthias Nöckel (Center for Economic Studies and ifo Institute (CESifo), 2018)
In this paper, we estimate a logit mixture vector autoregressive (Logit-MVAR) model describing monetary policy transmission in the euro area over the period 1999-2015. MVARs allow us to differentiate between different states of the economy. In our model, the time-varying state weights are determined by an underlying logit model. In contrast to other classes of non-linear VARs, the regime affiliation is neither strictly binary, nor binary with a transition period, and based on multiple variables. We show that monetary policy transmission in the euro area can indeed be described as a mixture of two states. The first (second) state with an overall share of 84% (16%) can be interpreted as a “normal state” (“crisis state”). In both states, output and prices are found to decrease after monetary policy shocks. During “crisis times” the contraction is much stronger, as the peak effect is roughly one-and-a-half times as large when compared to “normal times.” In contrast, the effect of monetary policy shocks is less enduring in crisis times. Both findings provide a strong indication that the transmission mechanism is indeed different for the euro area during times of economic and financial distress.
Keywords: C32; E52; E58; 330; economic and financial crisis; euro area; mixture VAR; monetary policy transmission; state-dependency